Temperature regimes during an artificial upwelling experiment (artificial upwelling treatments) - Yvonne Sawall; Ellias Yuming Feng (PANGAEA, 2020)
This dataset containes the data of three temperature loggers per AU treatment: 3 loggers in AU+50m in aquarium A1, A3, A5; 3 loggers in AU+100m in aquarium B1, B3, B5. AU+50m = constant 31°C + daily simulated upwelling from 50 m depth for 25 minutes AU+100m = constant 31°C + daily simulated upwelling from 100 m depth for 25 minutes
In: Sawall, Y; Feng, EY (2020): Temperature regimes and Coral response parameters of the artificial upwelling experiment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.921906